Embedding biological knowledge in a conceptual design tool. Issue 5 (2nd September 2016) - Becattini, Niccolò; Cascini, Getano; Rosa, Francesco
ABSTRACT: This paper presents a methodological tool to support the search for Natural Sources of Inspiration so as to spark new ideas in designers along Bio-Inspired Design activities. The proposed tool leverages the correlation between the NIST Functional Basis and the Biomimicry Taxonomy, to allow designers with no or scarce biological knowledge to search already existing databases of natural phenomena. The methodological framework is structured so that its implementation in a CAx system can be promisingly carried out. GRAPHICAL ABSTRACT: